The influence of seed treatment by protectants and microfertilizer on sowing qualities and biological indicators of winter bread wheat - O. Zaima; O. Kalitsinska (Карантин і захист рослин)
Goal. To determine the effect of various protectants and microfertilizer on sowing qualities and biological parameters of winter bread wheat seeds.